Diagnostic Modality in Spine Disease: A Review - Kim, Gang-Un; Chang, Min Cheol; Kim, Tae Uk; Lee, Gun Woo (Asian spine journal, 2020)
Spine diseases are common and exhibit several causes, including degeneration, trauma, congenital issues, and other specific factors. Most people experience a variety of symptoms of spine diseases during their lifetime that are occasionally managed with conservative or surgical treatments. Accurate diagnosis of the spine pathology is essential for the appropriate management of spine disease, and various imaging modalities can be used for the diagnosis, including radiography, computed tomography (CT), magnetic resonance imaging (MRI), and other studies such as EOS, bone scan, single photon emission CT/CT, and electrophysiologic test. Patient (or case)-specific selection of the diagnostic modality is crucial; thus, we should be aware of basic information and approaches of the diagnostic modalities. In this review, we discuss in detail, about diagnostic modalities (radiography, CT, MRI, electrophysiologic study, and others) that are widely used for spine disease.